2(n+2)=9(6-n)

Simple and best practice solution for 2(n+2)=9(6-n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(n+2)=9(6-n) equation:



2(n+2)=9(6-n)
We move all terms to the left:
2(n+2)-(9(6-n))=0
We add all the numbers together, and all the variables
2(n+2)-(9(-1n+6))=0
We multiply parentheses
2n-(9(-1n+6))+4=0
We calculate terms in parentheses: -(9(-1n+6)), so:
9(-1n+6)
We multiply parentheses
-9n+54
Back to the equation:
-(-9n+54)
We get rid of parentheses
2n+9n-54+4=0
We add all the numbers together, and all the variables
11n-50=0
We move all terms containing n to the left, all other terms to the right
11n=50
n=50/11
n=4+6/11

See similar equations:

| 11-4x=-7x+17 | | x/16+2X=33 | | 2(x-10)=-6+2 | | -13+7=x+9 | | 2(x-10)=6x+10 | | 7(2m-1)-(3/5)m=6/5(4-3m) | | (Xx2)+125=2059 | | 3r^2-3r+1=37 | | x^2-20x+181=0 | | 31-(2x+9)=2(x+6)+x | | 1+4x-8=0 | | 8a-(4a-3)=1 | | 12x-18+8x-12+x=180 | | 32=9/4x | | 42=x-19 | | 1/6x+3/2=-1/3 | | 6(x-6)+2=8(x+20-6 | | 3/11=x/x+9 | | (x-2)(x-5)=8 | | 1/4x=116 | | .2-1x+2.5=-3.6 | | a^2+(2a)^2=400 | | 13.5x=-7+94.5 | | 6x=19,5 | | 4y-3+y+33=7y+30-5y | | -8+3=-24+13x | | 4y-10+y+56=5y=50-2y | | 3v^+18v=0 | | -5(0.1x+0.2)-0.6=-0.1 | | 1.8x+3.6=6-4x+15 | | 2x=19/2 | | (6+u)(5u+9)=0 |

Equations solver categories